A return of economic intervention in advanced democracies after the financial and economic crisis (2008/2009)? - Zohlnhöfer, Reimut; Jathe, Jan; Engler, Fabian (Governance, 2024)
Did the financial and economic crisis (2008/2009) induce a permanent shift to more economic intervention in the advanced democracies? Three relevant theoretical perspectives are considered. First, the crisis could have led all governments to intervene more, irrespective of their partisan composition. Second, voter demand could have shifted towards more intervention due to the crisis, again inducing all governments to expand economic intervention. Third, increasing salience of economic issues could have led to an accentuation of partisan differences in economic policy which should have led to an expansion of economic intervention under left governments only. We present data from a new index of economic intervention, which show that governments increased economic intervention during the immediate crisis but returned to liberalization afterward. Similarly, statistical analyses show that partisan differences disappear during the acute crisis but return thereafter. Hence, the financial and economic crisis did not constitute a game-changer in economic policymaking in advanced democracies.
Zuerst veröffentlicht: 14. Juni 2024
Gesehen am 18.11.2024